Vkorc1 sequencing suggests anticoagulant resistance in rats in New Zealand. Issue 1 (25th May 2016) - Cowan, Phil E; Gleeson, Dianne M; Howitt, Robyn LJ; Ramón‐Laca, Ana; Esther, Alexandra; Pelz, Hans‐Joachim
Abstract: BACKGROUND: Anticoagulant toxins are used globally to control rats. Resistance of Rattus species to these toxins now occurs in at least 18 countries in Europe, America and Asia. Resistance is often associated with single nucleotide polymorphisms (SNPs) in the Vkorc1 gene. This study gives a first overview of the distribution and frequency of Vkorc1 SNPs in rats in New Zealand. New Zealand is unusual in having no native rodents but three species of introduced Rattus – norvegicus Berk., rattus L. and exulans Peale. RESULTS: Sequence variants occurred in at least one species of rat at all 30 of the sites sampled. Three new SNPs were identified, one in kiore and two in ship rats. No SNPs previously associated with resistance were found in Norway rats or kiore, but seven ship rats were heterozygous and one homozygous for the A74T variant. Its resultant Tyr25Phe mutation has previously been associated with resistance to both first‐ and second‐generation anticoagulants in ship rats in Spain. CONCLUSIONS: This is the first evidence of potential resistance to anticoagulant toxins in rats in New Zealand. Further testing using blood clotting response times in dosed rats is needed to confirm resistance potentially conferred by the Tyr25Phe mutation. Assessment is also needed of the potential of the other non‐synonymous variants (Ala14Val, Ala26Val) recorded in this study to confer resistance to anticoagulant toxins. © 2016 Society of Chemical Industry